Impacts of sexual harassment in schools and institutions of higher education on victims’ academic performance: a Malaysian perspective - Ali Mohamed, Ashgar Ali (penseejournal.com, 2014)
Sexual harassment is one of the contemporary silent issues in the academic setting such as schools and institutions of higher education in Malaysia. The above subject has become a climax discourse and heatedly debated in various sectors in the recent past. Specifically, despite advocacy of no discrimination between female and male in education, sexual harassment in schools and higher educational institutions has drastically prevalent. A number of theoretical and empirical studies in different parts of the world have demonstrated that sexual harassment has a tendency of causing long term psychological disturbances to the victims. Undeniably, the effect of sexual harassment in schools and institutions of higher education on students’ academic performance is not appropriately drawn attention in Malaysia. In light of the above, the primary aim of this paper is to explore, firstly, the sexual harassment scenarios in the Malaysian educational sectors and, secondly, the impacts of sexual harassment on victims with special emphasis on their academic performance. This article also discusses the health and financial implications of sexual harassment on the victims and the economy of the country respectively.